Longitudinal scintigraphic study of parotid and submandibular gland function after total body irradiation in children and adolescents - MATS BÅGESUND, SVEN RICHTER, OLLE RINGDÉN, & GÖRAN DAHLLÖF (IAPD and Blackwell, 2007)
Total body irradiation (TBI) and cyclophosphamide (CY) during allogeneic stem cell transplantation (ASCT) cause salivary gland dysfunction in children.